1994
DOI: 10.1152/jn.1994.72.3.1402
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of propagating waves in the olfactory network of a terrestrial mollusk: an electrical and optical study

Abstract: 1. The procerebral (PC) lobe of the terrestrial mollusk Limax maximus contains a highly interconnected network of local olfactory interneurons that receives ipsilateral axonal projections from superior and inferior noses. This network exhibits an approximately 0.7-Hz intrinsic oscillation in its local field potential (LFP). 2. Intracellular recordings show that the lobe contains at least two classes of neurons with activity phase locked to the oscillation. Neurons in one class produce periodic bursts of spikes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
132
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(144 citation statements)
references
References 43 publications
11
132
1
Order By: Relevance
“…Earlier optical and electrophysiological recordings confirmed that the PC contains at least two classes of neurons: bursting and non-bursting neurons (Ermentrout et al 1998;Kleinfeld et al 1994;Nikitin et al 2005). In the PC of Limax, bursting and non-bursting cells have been distinguished on the basis of their size, shape, and conduction velocity and it has been suggested that the somata of bursting neurons are larger than those of the non-bursting neurons (Watanabe et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier optical and electrophysiological recordings confirmed that the PC contains at least two classes of neurons: bursting and non-bursting neurons (Ermentrout et al 1998;Kleinfeld et al 1994;Nikitin et al 2005). In the PC of Limax, bursting and non-bursting cells have been distinguished on the basis of their size, shape, and conduction velocity and it has been suggested that the somata of bursting neurons are larger than those of the non-bursting neurons (Watanabe et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…PC neurons display a resting cyclic electrical activity of 0.7 Hz, which is important for the storage of odor memory and odor discrimination (Balaban and Maksimova 1993;Delaney et al 1994;Gelperin and Tank 1990;Schütt et al 2000). This oscillatory activity was shown to be modulated by odor stimuli Gelperin and Tank 1990;Gervais et al 1996;Kimura et al 1998;Kleinfeld et al 1994) and by signal molecules such as nitrogen and carbon monoxide, c-aminobutyric acid, 5-hydroxytryptamine (5-HT), dopamine (DA), glutamate (Glu), acetylcholine (ACh) and endogenous neuropeptides such as FMRFa and catch-relaxing peptide, which are present in the PC Cooke and Gelperin 1988;Elekes and Nassel 1990;Gelperin et al 1993Gelperin et al , 2000Hernadi et al 1995;Inoue et al 2001;Kobayashi et al 2010). It was observed that 5-HT and DA excited PC neurons and promoted transitions from steady to bursting activity.…”
Section: Introductionmentioning
confidence: 99%
“…Since NB cells, but not B cells, project to the internal neuropil it is assumed that NMDA-receptor-like immunoreactivity belongs to NB cells in the PC. If it is considered that B cells are the main source of Glu [12], then a glutamatergic input that evokes NO synthesis on NB cells seems reasonable (see Fig. 6.).…”
Section: Glu Is a Potential Endogenous Inducer Of No Synthesis In The Pcmentioning
confidence: 98%
“…Track tracing experiments have revealed the members of the neuronal afferents and the types and morphology of PC interneurons [5,6,7,8,9,10]. In addition to morphological findings, electrophysiological recording has also demonstrated that the population of PC cells within the layer where the perikarya of PC interneurons are located (the cell mass layer) consists of large number (75%) of non-bursting (NB) neurons with small size (5-8 μm), and a smaller number (25%) of bursting (B) neurons of larger size (10-15 μm) [11,12].…”
Section: Introductionmentioning
confidence: 98%
“…The PC lobe also propagates activity waves from its apical to basal pole at 1.1 mm/sec in vitro Kimura et al, 1998b;Kleinfeld et al, 1994). The activity waves serve to separate odor representations set up in the PC lobe by associative conditioning when odors are used as conditioned stimuli Gelperin, 1999;Kimura et al, 1998a).…”
Section: Introductionmentioning
confidence: 99%